1952
DOI: 10.2136/sssaj1952.03615995001600010023x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Its Influence on Tilth of Soils

Abstract: The purpose of this study was to determine some of the changes that have taken place in the structure of several Corn Belt soils and its influence on tilth, permeability, volume weight, and percent of pores drained. Samples of soil were examined in the field to determine the type, class, and grade of structure, direction of natural fracture when lumps were broken, and size and number of visible pores. Six to twelve undisturbed soil core samples 3 inches thick and 3 inches in diameter were taken at random from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1954
1954
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…As the results revealed, the highest amount of erosion was the result of the conversion of rangelands to agricultural lands due to reduction of soil organic matters and increased soil compaction that was also observed in the results of previous studies [74,75]. Another land use change that has had a great effect on erosion is the conversion of forest into rangelands and agricultural lands that has also been observed in studies by Mancino et al [76] and Wynants et al [77].…”
Section: Discussionsupporting
confidence: 71%
“…As the results revealed, the highest amount of erosion was the result of the conversion of rangelands to agricultural lands due to reduction of soil organic matters and increased soil compaction that was also observed in the results of previous studies [74,75]. Another land use change that has had a great effect on erosion is the conversion of forest into rangelands and agricultural lands that has also been observed in studies by Mancino et al [76] and Wynants et al [77].…”
Section: Discussionsupporting
confidence: 71%
“…These data, along with those from other research stations were used to assign values to individual soils. Soils were then classified based on actual observations and measurements Klingebiel, 1950, 1952;Klingebiel and O'Neal, 1952).…”
Section: Engineering Interpretationsmentioning
confidence: 99%
“…Soil aggregation and organic matter changes were found to depend upon cropping treatment, as well as upon soil erosion (Wilson and Browning, 1945;Van Bavel and Schaller, 1950). Several studies evaluating the effects of tillage and cropping practices on soil tilth (Slipher, 1932;Faulkner, 1943;Browning and Norton, 1947;Lyon et al, 1950;Van Doren and Klingebiel, 1952;Klingebiel and O'Neal, 1952;Neal, 1953;and Melsted, 1954) found that under virgin conditions, the combination of structure, aggregation, organic matter content, and porosity resulted in nearly ideal soil tilth. The net effect of tillage practices, however, was decreased soil aggregation and organic matter content, and increased compaction and soil erosion; therefore, the result was reduced soil tilth.…”
Section: Introductionmentioning
confidence: 99%